A Rare Case Report of a Tail-Gut Cyst from a Gynecological Point of View - George Maroudias; Alina-Roxani Gouloumi; Zoi Tsakiraki; Maria Oikonomou; George Chrelias; Charalampos Chrelias (Tehran University of Medical Sciences, 2018)
A tail-gut cyst can be often a misleading clinical entity. In half of the patients there is no presenting symptom. On the other half, the patients most commonly present with a variety of symptoms such as rectal pain, constipation, lower back pain, dysuria or dyspareunia. The recommended treatment of choice for the tail-gut cyst is complete surgical excision without rupture of the cyst. We present the case of a 29-year-old female with history of dyspareunia over a 5-month period, who discovered an "ovarian" cyst during an annual scheduled ultrasound appointment. However, the intraoperative findings were surprising. The bottomline is always to keep in mind the Pandora's Box of the retrorectal space.